Instructional Space Management Skills and Learning Autonomy among TECH-VOC Students in Carmen District, Davao Del Norte - Sanorjo, Mark Angelo (Yayasan Sembilan Pemuda Indonesia, 2024)
In this study, instructional space management skills is a measure expected to improve the learning autonomy of the tech-voc students. In this study, the researcher selected the 150 junior high school students in Carmen District, Davao del Norte as the respondents of the study. Findings revealed that teachers’ instructional space management skills was rated as extensive, while, learning autonomy of the tech-voc students in Carmen District in Davao del Norte was described as moderately extensive. Further, correlation analysis demonstrated that there is a significant relationship between teachers’ instructional space management skills and learning autonomy of the tech-voc students in Carmen District in Davao del Norte. Evidently, regression analysis proved that instructional space management skills in terms of engaging and interactive learning; growth mindset; and inclusivity and diversity were significant predictors of learning autonomy of the tech-voc students in Carmen District in Davao del Norte. The study, therefore, conducted for further utilization of findings through publication in reputable research journal.